Analysing observable success and activity indicators on crowdfunding platforms. (2015) - Lechtenbörger, Jens; Stahl, Florian; Volz, Vanessa; Vossen, Gottfried
Crowdfunding, a strategy for obtaining financial support for a project, an event, or a start-up company, has become both popular and successful in recent years. However, research on the subject is still scarce. Based on data from Kickstarter (US-based) and Startnext (Germany-based) projects, insights into the current crowdfunding situation at the aforementioned popular crowdfunding platforms are provided in this paper. Furthermore, project development over time is presented with regard to observable success and activity indicators, in particular focusing on activities such as communication within and growth of the community formed by project initiators and supporters.